Efek Pemberian Ekstrak Etanol Kulit Batang Bau Langit (Cyathocalyx sumatranus Scheff.) terhadap Struktur Lambung Tikus (Rattus norvegicus) yang Diinduksi Parasetamol (Isolation and Analysis of Proteolytic Activity of Local Actinomycetes from Aceh, Indone - Widya Sari; Masykur Masykur; Putri Novita Sari; Fauziah Fauziah; Rosnizar Rosnizar (Jurnal Bioleuser, 2024)
The purpose of this study was to determine the gastroprotective activity of ethanol extract of bau langit stem bark in the stomachs of paracetamol-induced rats. This research uses experimental method. Data analysis used a completely randomized design (CRD) with 5 treatments and 5 replicates. All treatments except normal control (K0) in esophageal intubation of paracetamol at a dose of 1350 mg/kg BB. Negative control (K-) is given aqueous for 14 days. P1, P2 and P3 treatments were given Cyathocalyx sumatranus extract of 150 mg/kg BB, 300 mg/kg BB and 600 mg/kg BB respectively. The treatment was given for 14 days and on the 7th day paracetamol was induced. Samples of gastric tissue were made histopathological preparations with paraffin method and hematoxylin-eosin (HE) staining. The variables observed include desquamation, erosion and ulceration of the gastric mucosa. The results showed that the gastric mucosa treated with K0, K-, P1 and P2 was desquamated. Erosion occurs in the treatment of K-. Ulceration was not found in all treatments. Paracetamol at a dose of 1350 mg/kgBB can induce erosion. The conclusion of this study is that the administration of C. sumatranus extract at doses of 300 mg/kgBB and 600 mg/kg BB is able to reduce gastric mucosal erosion due to paracetamol induction, while the dose of 150 mg/kg BB of C. sumatranus extract has not been able to prevent gastric mucosal damage.